Prevalence and Risk Factors of Vision Impairment among Children of Employees of Telecom, Italy. Issue 4 (July 2016) - Nucci, Carlo; Cofini, Vincenza; Mancino, Raffaele; Ricci, Federico; Martucci, Alessio; Cecilia, Maria Rosita; Ciciarelli, Vincenzo; Zazzara, Francesca; Cedrone, Claudio; di Orio, Ferdinando
Purpose: To define the prevalence, causes, and risk factors of vision impairment (VI) in children. Methods: In this study, relatives of Association for Supplemental Health Insurance to the Employees of Telecom members aged 5-16 years were examined in all Italian regions. A standardized record card was used to collect data on medical history; keratometry; objective refraction; uncorrected, presenting, and best-corrected visual acuity (VA); examination of the pupils, adnexa, and anterior segment; direct ophthalmoscopy; posterior segment and fundus examination; and assessment for ocular pathology. Binocular and monocular VI were defined by a VA <5/10 (or <20/40). Results: The campaign included 17, 508 children, 12, 798 of whom (73.1%) were examined (and 12, 740 on whom all VA data were gathered). The prevalence of uncorrected, presenting, and best-corrected VI in the better eye was 9.0%, 2.51%, and 0.10%, respectively. The following variables were associated with presenting VI: age 10-16 years, family history of myopia, female sex, family history of keratoconus, and hypertension. Myopia is the main cause of VI (82.6%). A total of 96% of children with presenting VI had correctable VI. Conclusions: Correctable VI because of myopia is an important public health problem in school-age children in Italy.